Bacterial protein acetylation: mechanisms, functions, and methods for study - Rizo, Jocelin; Encarnación-Guevara, Sergio (Frontiers in Cellular and Infection Microbiology, 2024)
Lysine acetylation is an evolutionarily conserved protein modification that changes protein functions and plays an essential role in many cellular processes, such as central metabolism, transcriptional regulation, chemotaxis, and pathogen virulence. It can alter DNA binding, enzymatic activity, protein-protein interactions, protein stability, or protein localization. In prokaryotes, lysine acetylation occurs non-enzymatically and by the action of lysine acetyltransferases (KAT). In enzymatic acetylation, KAT transfers the acetyl group from acetyl-CoA (AcCoA) to the lysine side chain. In contrast, acetyl phosphate (AcP) is the acetyl donor of chemical acetylation. Regardless of the acetylation type, the removal of acetyl groups from acetyl lysines occurs only enzymatically by lysine deacetylases (KDAC). KATs are grouped into three main superfamilies based on their catalytic domain sequences and biochemical characteristics of catalysis. Specifically, members of the GNAT are found in eukaryotes and prokaryotes and have a core structural domain architecture. These enzymes can acetylate small molecules, metabolites, peptides, and proteins. This review presents current knowledge of acetylation mechanisms and functional implications in bacterial metabolism, pathogenicity, stress response, translation, and the emerging topic of protein acetylation in the gut microbiome. Additionally, the methods used to elucidate the biological significance of acetylation in bacteria, such as relative quantification and stoichiometry quantification, and the genetic code expansion tool (CGE), are reviewed.). Furthermore, it was found that Acs is activated by CobB, a bacterial protein deacetylase homologous to yeast Sir2, which specifically hydrolyzes the acetyl group of the acetyl-lysine active site of Acs to promote its activity (Starai et al., 2002; Starai et al., 2004). Since then, acetylation in bacteria has been shown to regulate several fundamental pathways, including cellular function, physiology, and metabolism. Proteomics studies have found that in some bacteria, the proteins acetylated on lysine constitute more than 10% of the proteome.